Structure and stability of γ1‐AuZn2.1: a γ‐brass‐related complex phase in the Au–Zn System. Issue 6 (7th December 2020) - Koley, Biplab; Thimmaiah, Srinivasa; Lidin, Sven; Jana, Partha P.
Abstract : The synthesis, crystal structure and stability of the γ‐brass‐related complex phase γ1 ‐AuZn2.1 in the Au–Zn binary system are reported. The compound has been described as consisting of two main building units, i.e. a 38‐atom modified Pierce cluster and an intergrown 19‐atom double icosahedron. Abstract : γ1 ‐AuZn2.1 in the Au–Zn binary system has been synthesized and its structure analyzed by single‐crystal X‐ray diffraction. It crystallizes in the trigonal space group P 31 m (No. 157) with ∼227 atoms per unit cell and represents a 3 a × 3 a × c superstructure of rhombohedrally distorted γ‐Au5– x Zn8+ y . The structure is largely tetrahedrally closed packed. The formation of γ1 ‐AuZn2.1 can be understood within the framework of a Hume‐Rothery stabilization mechanism with a valence electron concentration of 1.68 e/a (valence electrons per atom).